La motricidad en el triatlón: otra mirada desde la física hacia la biomecánica (2021)
The present article is of scientific research, it addresses aspects of motor skills supported by the foundations of biomechanics, in the presence of physical and interdisciplinary reasoning. These sciences in high school reveal an approach to the study of man in the execution of movement. Understanding about motor skills increases the interest of the student-athletes of the school sports initiation school. And at the same time they are indispensable in the Physical Culture career, as the internal structure of the body in joint and muscular movement. Didactic proposals are sought to introduce these contents, thus achieving a comprehensive general culture and training them professionally.